Postfeminism at play: Pretend play with Disney princess transmedia in the early childhood education classroom - Valade, Tifanie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2023)
This article examines how young children take up gender and sexuality discourses embedded in Disney Princess transmedia narratives and merchandise. A feminist ethnographic study conducted in two Canadian early childhood education and care (ECEC) classrooms found that young children often take up stereotypically gendered, heteronormative roles from princess transmedia during pretend play. The author contends that princess play includes problematic postfeminist themes, yet also offers agentic, pleasurable roles for children to embody. Disney’s hyperfeminine princess aesthetic is sometimes utilized by girls to subvert inequitable gender hierarchies and claim powerful positions within play scenarios. However, femmephobia can result in reinforcement of hegemonic gender discourses via gender policing. Implications for gender equity in ECEC environments are discussed.